**NCERT
Solutions for Class 7 Maths Chapter 12 Algebraic Expressions Ex 12.3**

NCERT Solutions for Class 7 Maths Chapter 12 Algebraic
Expressions Ex 12.3 are the part of NCERT Solutions for Class 7 Maths. Here you
can find the NCERT Solutions for Class 7 Maths Chapter 12 Algebraic Expressions
Ex 12.3.

**NCERT Solutions for Class 7 Maths Chapter 12 Algebraic Expressions Ex 12.1****NCERT Solutions for Class 7 Maths Chapter 12 Algebraic Expressions Ex 12.2****NCERT Solutions for Class 7 Maths Chapter 12 Algebraic Expressions Ex 12.3****NCERT Solutions for Class 7 Maths Chapter 12 Algebraic Expressions Ex 12.4**

**Ex
12.3 Class 7 Maths Question 1.**

If m = 2, find the value of:(i) m – 2

(ii) 3m – 5

(iii) 9 – 5m

(iv) 3m

^{2}– 2m – 7

(v) 5m/2 − 4

**Solution:
**(i) m – 2

Putting m = 2, we get

m – 2 = 2 – 2 = 0

(ii) 3m – 5

Putting m = 2, we get

3m – 5 = 3 × 2 – 5 = 6 – 5 = 1

(iii) 9 – 5m

Putting m = 2, we get

9 – 5m = 9 – 5 × 2 = 9 – 10 = -1

(iv) 3m^{2} – 2m – 7

Putting m = 2, we get

3m^{2} – 2m – 7 = 3(2)^{2} – 2(2) – 7 = 3 × 4 – 4 – 7

= 12 – 4 – 7 = 12 – 11 = 1

(v) 5m/2 − 4

Putting m = 2, we get

5m/2 – 4 = (5 × 2)/2 – 4 = 5 – 4 = 1

**Ex 12.3 Class 7 Maths Question 2.**

If p = -2, find the value of:(i) 4p + 7

(ii) -3p

^{2}+ 4p + 7

(iii) -2p

^{3}– 3p

^{2}+ 4p + 7

**Solution:
**(i) 4p + 7

Putting p = -2, we get

4p + 7 = 4(-2) + 7 = -8 + 7 = -1

(ii) -3p^{2} + 4p + 7

Putting p = -2, we get

-3p^{2} + 4p + 7 = -3(-2)^{2} + 4(-2) + 7

= -3 × 4 – 8 + 7 = -12 – 8 + 7 = -13

(iii) -2p^{3} – 3p^{2} +
4p + 7

Putting p = -2, we get

-2p^{3} – 3p^{2} + 4p + 7 = –2(-2)^{3} –
3(-2)^{2} + 4(-2) + 7

= -2 × (-8) – 3 × 4 – 8 + 7

= 16 – 12 – 8 + 7 = 3

**Ex 12.3 Class 7 Maths Question 3.**

Find the value of the following expressions, when x
= –1:(i) 2x – 7

(ii) – x + 2

(iii) x^{2 }+ 2x + 1

(iv) 2x^{2 }– x – 2

**Solution:**

Putting x = –1 in each expression, we get**
**(i) 2x – 7 = 2(–1) – 7 = –2 – 7 = –9

(ii) –x + 2 = –(–1) + 2 = 1 + 2 = 3

(iii) x^{2 }+ 2x + 1 = (–1)^{2} + 2(–1)
+ 1 = 1 – 2 + 1 = 0

(iv) 2x^{2 }– x – 2 = 2(–1)^{2} – (–1)
– 2 = 2 + 1 – 2 = 1

**Ex 12.3 Class 7 Maths Question 4.**

If a = 2, b = -2, find the value of:(i) a

^{2}+ b

^{2}

(ii) a

^{2}+ ab + b

^{2}

(iii) a

^{2}– b

^{2}

**Solution:
**(i) a

^{2}+ b

^{2}

Putting a = 2 and b = -2, we get

a

^{2}+ b

^{2}= (2)

^{2}+ (-2)

^{2}= 4 + 4 = 8

(ii) a^{2} + ab + b^{2}

Putting a = 2 and b = -2, we get

a^{2} + ab + b^{2} = (2)^{2} + 2(-2) + (-2)^{2} =
4 – 4 + 4 = 4

(iii) a^{2} – b^{2}

Putting a = 2 and b = -2, we get

a^{2} – b^{2} = (2)^{2} – (-2)^{2} =
4 – 4 = 0

**Ex 12.3 Class 7 Maths Question 5.**

When a = 0, b = -1, find the value of the given
expressions:(i) 2a + 2b

(ii) 2a

^{2}+ b

^{2}+ 1

(iii) 2a

^{2}b + 2ab

^{2}+ ab

(iv) a

^{2}+ ab + 2

**Solution:**

Putting a = 0, b = -1 in each expression, we get**
**(i) 2a + 2b = 2(0) + 2(-1) = 0 – 2 = -2

(ii) 2a^{2} + b^{2} + 1 =
2(0)^{2} + (-1)^{2} + 1 = 0 + 1 + 1 = 2

(iii) 2a^{2}b + 2ab^{2} + ab =
2(0)^{2}(-1) + 2(0)(-1)^{2} + (0)(-1)

= 0 + 0 + 0 = 0

(iv) a^{2} + ab + 2 = (0)^{2} +
(0)(-1) + 2 = 0 + 0 + 2 = 2

**Ex 12.3 Class 7 Maths Question 6.**

Simplify the expressions and find the value if x is
equal to 2.(i) x + 7 + 4(x – 5)

(ii) 3(x + 2) + 5x – 7

(iii) 6x + 5(x – 2)

(iv) 4(2x – 1) + 3x + 11

**Solution:
**(i) x + 7 + 4(x – 5) = x + 7 + 4x – 20 = 5x – 13

Putting x = 2, we get

5x – 13 = 5 × 2 – 13 = 10 – 13 = -3

(ii) 3(x + 2) + 5x – 7 = 3x + 6 + 5x – 7 = 8x – 1

Putting x = 2, we get

8x – 1 = 8 × 2 – 1 = 16 – 1 = 15

(iii) 6x + 5(x – 2) = 6x + 5x – 10 = 11x – 10

Putting x = 2, we get

11x – 10 = 11 × 2 – 10 = 22 – 10 = 12

(iv) 4(2x – 1) + 3x + 11 = 8x – 4 + 3x + 11 = 11x +
7

Putting x = 2, we get

11x + 7 = 11 × 2 + 7 = 22 + 7 = 29

**Ex 12.3 Class 7 Maths Question 7.**

Simplify these expressions and find their values if
x = 3, a = -1, b = -2.(i) 3x – 5 – x + 9

(ii) 2 – 8x + 4x + 4

(iii) 3a + 5 – 8a + 1

(iv) 10 – 3b – 4 – 5b

(v) 2a – 2b – 4 – 5 + a

**Solution:
**(i) 3x – 5 – x + 9 = 2x + 4

Putting x = 3, we get

2x + 4 = 2 × 3 + 4 = 6 + 4 = 10

(ii) 2 – 8x + 4x + 4 = -8x + 4x + 2 + 4 = -4x + 6

Putting x = 2, we have

-4x + 6 = -4 × 3 + 6 = -12 + 6 = -6

(iii) 3a + 5 – 8a + 1 = 3a – 8a + 5 + 1 = -5a + 6

Putting a = -1, we get

-5a + 6 = -5(-1) + 6 = 5 + 6 = 11

(iv) 10 – 3b – 4 – 5b = -3b – 5b + 10 – 4 = -8b + 6

Putting b = -2, we get

-8b + 6 = -8(-2) + 6 = 16 + 6 = 22

(v) 2a – 2b – 4 – 5 + a = 2a + a – 2b – 4 – 5 = 3a –
2b – 9

Putting a = -1 and b = -2, we get

3a – 2b – 9 = 3(-1) – 2(-2) – 9

= -3 + 4 – 9 = 1 – 9 = -8

**Ex 12.3 Class 7 Maths Question 8.**

(i) If z = 10, find the value of z^{2}– 3(z – 10).

(ii) If p = -10, find the value of p

^{2}– 2p – 100.

**Solution:
**(i) z

^{2}– 3(z – 10) = z

^{2}– 3z + 30

Putting z = 10, we get

z

^{2}– 3z + 30 = (10)

^{2}– 3(10) + 30

= 100 – 30 + 30 = 100

(ii) p^{2} – 2p – 100

Putting p = -10, we get

p^{2} – 2p – 100 = (-10)^{2} – 2(-10) – 100

= 100 + 20 – 100 = 20

**Ex 12.3 Class 7 Maths Question 9.**

What should be the value of *a*if the value of 2x

^{2}+ x – a equals to 5, when x = 0?

**Solution:
**When x = 0, 2x

^{2}+ x – a = 5

Putting x = 0, we get

2(0)

^{2}+ (0) – a = 5

0 + 0 – a = 5

-a = 5

Or, a = -5 which is required value of a.

**Ex 12.3 Class 7 Maths Question 10.**

Simplify the expression and find its value when a =
5 and b = -3.2(a

^{2}+ ab) + 3 – ab

**Solution:
**2(a

^{2}+ ab) + 3 – ab = 2a

^{2}+ 2ab + 3 – ab

= 2a

^{2}+ 2ab – ab + 3

= 2a

^{2}+ ab + 3

Putting, a = 5 and b = -3, we get

2a

^{2}+ ab + 3 = 2(5)

^{2}+ (5)(-3) + 3

= 2 × 25 – 15 + 3

= 50 – 15 + 3

= 53 – 15 = 38

Hence, the required value of the expression is 38.

**You can also like these:**

**NCERT Solutions for Maths Class 8**

**NCERT Solutions for Maths Class 9**

**NCERT Solutions for Maths Class 10**

**NCERT Solutions for Maths Class 11**